Pehitungan PPh Pasal 21 untuk Pegawai Tidak Tetap dan Pegawai Dengan Upah Harian Dengan Metode Nett - Dewi, Ririn Sari; A, Aerlangga; Fadli, H Subhan (Nanggroe: Jurnal Pengabdian Cendikia, 2025)
This community service aims to provide counseling and understanding in tax article 21 related to calculations using the net method. The target of this service is PT Aliya Pratama Mandiri Employees. The problem that occurs at PT Aliya Pratama Mandiri is still a lack of understanding of tax problems. The implementation is carried out with training and mentoring using the material presentation method and continued with discussion and questions and answers. Evaluation of this stage is carried out by collecting and concluding data from each stage of the activity. The results of the study are expected to show that: it can provide an overview and solution to the calculation of PPh 21 using the net method.